Planning a New Business: Typical Mistakes of a Business Plan in the Service Sector - JUKOVA, Evgeniya E.; ILINA, Irina Y.; GUNDARIN, Mikhail V.; POTEKHINA, Elena V.; MISANOVA, Irina N.; ZOTOVA, Alexandra I. (Journal of Environmental Management and Tourism; Vol 10 No 2 (2019): JEMT VOlume X Issue 2(34) Spring 2019DO - 10.14505//jemt.v10.2(34).22, 2019)
According to the statistics, only five percent of the beginning entrepreneurs achieve success and stay afloat. Anyone who has the money can establish a business, but far from everyone can take advantage of opportunities and not become discouraged because of difficulties. Startups start working in the chosen area and do not take into account the business peculiarities of the service sector (or do not know about them), and later pay with their own failure. Thus, analysis of typical mistakes and the development of recommendations are interesting and promising. The article shows the main mistakes of business planning in the service sphere that are the most frequent ones in practice. Their causes and consequences are considered. Recommendations to eliminate these mistakes are made. The article will be useful to a wide range of readers: both beginning entrepreneurs who are only thinking about starting their own business and TOP managers who want to expand their business.